The evolution of phototrophic Fe(II)-oxidizing bacteria shaping the distribution of iron-bound phosphorus in water columns - Huang, Shan; Yuanyuan Ren; Chao Peng; Chao Zhong; Jiahao Chen; Yurong Deng; Geng Wu; Yuanyuan Liu; Dong, Hailiang; Juan Liu (Chemical Geology, 2026)
The evolution of Fe(II)-oxidizing microorganisms has been closely linked to the evolution of Earth's iron biogeochemical cycle and redox history. However, its impact on the coupled biogeochemical cycling of iron and phosphorus, particularly the distribution of iron-bound phosphate (PFe) in water columns, remains largely unexplored. This study elucidates the distinct Fe(II) oxidation mechanisms of the anoxygenic Rhodobacter ferrooxidans SW2 and the oxygenic Synechococcus sp. PCC 7002, along with the properties, transformation processes, and phosphate interactions of their biogenic iron (oxyhydr)oxides. SW2-mediated Fe(II) oxidation via iron oxidase drove sequential transformation from ferrihydrite to green rust and then to goethite. The resulting cell-mineral aggregates had a large hydrodynamic diameter (Dh, up to 26 μm), a high Fe/C ratio (∼2.5), and a rapid sedimentation rate (up to 57.7 m/day), efficiently transporting PFe to deep-sea sediments. In contrast, PCC 7002 indirectly oxidized Fe(II) via oxygen production, forming poorly crystalline iron (oxyhydr)oxides stabilized by extracellular polymeric substances. The resultant small aggregates (Dh = ∼6.9 μm), with a slower sedimentation rate (∼3.9 m/day), exhibited high phosphorus retention and were susceptible to dissimilatory iron reduction, facilitating PFe recycling in surface waters. These findings suggest that biogenic iron (oxyhydr)oxides from anoxygenic iron oxidizers act as carriers, transporting phosphorus to deep sediments, whereas those from oxygenic cyanobacteria function as phosphorus traps in surface waters. This study provides new insights into how the evolution of Fe(II)-oxidizing microorganisms reshapes PFe cycling and distribution in water columns, emphasizing the need to integrate microbiological and geochemical perspectives in understanding Earth's biogeochemical cycles.